1988
DOI: 10.1111/j.1432-1033.1988.tb13968.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, anion binding and mechanism of Co(II)‐substituted bovine muscle carbonic anhydrase

Abstract: The binding of N; to Co(I1)-substituted bovine carbonic anhydrase 111 was measured at various pH values by spectrophotometric titrations. The apparent Ki values were found to increase with pH in the studied range between pH 5.8 and 8.9. The inhibition of C 0 2 hydration by N; was found to be essentially uncompetitive at all investigated pH values (pH 6.3 -8.9). The Ki values for the inkbition of k,,, are much smaller than those obtained in the spectrophotometric titrations indicating that an enzyme form with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…2-3) [16,21,22,32,33,35,39,[41][42][43]45,48,50]. In the wellcharacterized -class, hydrogen bonded residues Glu106 and Thr199 further hydrogen bonds with the metal-bound hydroxide via the Thr199 O atom (Fig.…”
Section: Catalytic Mechanism Of the -Class -Class And -Class Carmentioning
confidence: 96%
See 1 more Smart Citation
“…2-3) [16,21,22,32,33,35,39,[41][42][43]45,48,50]. In the wellcharacterized -class, hydrogen bonded residues Glu106 and Thr199 further hydrogen bonds with the metal-bound hydroxide via the Thr199 O atom (Fig.…”
Section: Catalytic Mechanism Of the -Class -Class And -Class Carmentioning
confidence: 96%
“…Although the five classes of CAs evolved independent from one another, kinetic analyses have shown three CA classes ( -, -and -) share the same two-step ping pong mechanism for the reversible hydration of carbon dioxide to bicarbonate (eq.2-3) [6,7,12,18,21,31,[34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Catalytic Mechanism Of the -Class -Class And -Class Carmentioning
confidence: 99%
“…This result differs with those for the α class carbonic anhydrases. Co substitution of the active site Zn in human CA II resulted in an enzyme with approximately 50% of the CO 2 hydration activity [144,145] even though X‐ray crystallography showed that the metal ion in the Co‐substituted human CA II has a tetrahedral coordination similar to Zn [146]. The possibility that the active site metal of authentic Cam from M. thermophila is Co instead of Zn remains to be determined.…”
Section: Properties Of Isolated Carbonic Anhydrases From the Archaeamentioning
confidence: 99%
“…This is demonstrated for three mutants of HCA III in Figure 2. The values of wild-type HCA III and T199S HCA III could not be determined because of denaturation of the enzyme at low pH; this for CA III has been estimated at 5.0 on the basis of spectroscopic and inhibition data for cobalt(II)-substituted bovine CA III (Ren et al, 1988a). The replacement Thr-199 -* Ser in HCA III did not place the apparent into the pH range of these measurements.…”
Section: Resultsmentioning
confidence: 97%